Physical simulation of remaining oil distribution in the 3rd-order architecture unit in beach sand reservoir - Liu, Taixun; Fawad, Nadir; Li, Chao; Li, Haitao; He, Ruiwu; Xu, Jian; Ahmad, Qazi Adnan (Frontiers in Earth Science, 2023)
Introduction: Oilfield development’s primary objective has changed in recent years as a result of a deeper focus on oilfield exploration and possible reservoir oil extraction. These days, the distribution and characteristics of residual oil are hot topics. Methodology: This research study provides a physical simulation of the remaining oil distribution in the third-order architectural unit in the beach reservoir. Based on the reservoir geometry and compositional sequence, the third-order architecture unit in a beach sand reservoir can be divided into three types: layered, plate-like, and trough-like architecture units. Results and Discussion: A water-flooding simulation experiment is performed to find the distribution pattern of remaining oil (shortened as RO and used hereafter) and the controlling effect of the mudstone interlayer. The simulation results revealed that in the layered architecture unit with reverse-graded bedding, RO is mainly distributed between interlayers and accumulates at the bottom in fine-grain sands. The horizontal distribution of the mudstone interlayer has a profound effect on blocking the longitudinal migration of fluid. Second, in the plate-like architecture unit with uniform grain size, RO is mainly found in the middle portion of the model, separated by clay interlayers, with irregular presence of RO in the upper and lower part of the model. The oblique distribution of the clay interlayer has a significant effect on blocking the lateral migration of the fluid. Thirdly, in the trough-like architectural unit with normal-graded bedding, the RO is mainly distributed on top of the model in fine-grain sands and on the ridge-like parts formed by the interlayer’s intersection. Conclusion: A trough-like clay interlayer can promote fluid movement. RO distribution patterns from the current experiment can be used to explore the remaining oil in beach sand reservoirs of similar oilfields.